Emergency war surgery the survivalist's medical desk reference (Skyhorse Publishing, 2012)
The most advanced medical techniques used by military doctors in the field. Military surgeons must assume a leadership role in combat casualty care in circumstances that are far less than ideal. This handbook provides much of the information needed to tackle these issues and features state-of-the-art principles and practices of forward trauma surgery as used by military physicians in far flung locations around the globe. Featuring nearly 200 illustrations demonstrating proper techniques, Emergency War Surgery is the most trusted and up-to-date manual offered by the Department of Defense for military medical personnel in the field.